User experience analysis in virtual museums - Aleksandra Kobylska; Mariusz Dzieńkowski (Journal of Computer Sciences Institute)
The paper presents an analysis of user experience in virtual museums. The objects of interest are museums that offer a virtual walk which allows the user to visit and view exhibitions without leaving home. Among the selected objects for the study were the Museum of Auschwitz-Birkenau and the Malbork Castle Museum. The interfaces of these two virtual museums were subjected to eye tracking analysis using the Gazepoint GP3 HD eye tracker and an expert analysis using Nielsen heuristics. Additionally, a survey consisting of questions from the System Usability Scale and self-reported questions was then conducted to help gather information on usability and to collect opinions about online museums. The research group consisted of sixteen students from the Lublin University of Technology, who were presented with the same tasks to perform in the virtual museums. As a result of the research, it turned out that both according to the Nielsen heuristics and the System Usability Scale survey, the Auschwitz-Birkenau Museum was rated better, while in the eye tracking experiment both museums obtained similar results.